1967
DOI: 10.1038/icb.1967.14
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Follicular Structures in the Human Thymus at Autopsy

Abstract: Summary.A survey of 928 ;iiifopsy ihymie glands from hospital and accident deatlis was carried init lo dcterdiine the incidence of follicular structures in the human tliyinic incdulla. It was foiintl that, contrary to previous opinions, follicLilar structures with pale centres are indeed common in the norinal human tliyuius. The incidence in youn^ people is identical with the figure quoted for myasthenia gravis. Follicles tire not present in nconatcs and the incidence decreases with illness and with advancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…The antigen(s) involved can be 'non-self' and a component of a normal immune response or 'self' and a component of an autoimmune process. The findings serve to reinforce the previously indicated need for caution in attaching pathological significance to the mere presence of lymphoid follicles in the human thymus [14,15,28] and in the use of the term thymic hyperplasia [13] if any follicles are discovered in sections of a thymus.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The antigen(s) involved can be 'non-self' and a component of a normal immune response or 'self' and a component of an autoimmune process. The findings serve to reinforce the previously indicated need for caution in attaching pathological significance to the mere presence of lymphoid follicles in the human thymus [14,15,28] and in the use of the term thymic hyperplasia [13] if any follicles are discovered in sections of a thymus.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have found a lower prevalence of thymic lymphoid follicles in subjects dying after some time in hospital than is found in [14,24]. These studies suggested that this decreased prevalence is a stress effect and that the stress has to be present for some days.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Indeed, prominent intrathymic germinal center formation has been described in only two other clinical settings, e.g., SLE [15,73] and thyrotoxicosis [107]. Smaller and less numerous follicles may be present in thymus glands of healthy individuals [77,126]. Germinal center formation in peripheral lymph nodes occurs in response to the local trapping of antigen.…”
Section: Frequency and Localizationmentioning
confidence: 99%
“…Firstly, the presence of lymphoid follicles in human thymus which Mackay et al (1968) term 'thymitis' is not specific for myasthenia gravis. Lymphoid follicles are readily detectable in many young subjects who die suddenly (Middleton, 1967), or who have operations to correct congenital heart disease (Henry, 1968;Vetters and Barclay, 1973). Further, lymphoid follicles are seen frequently in other diseases now believed to have an autoimmune basis-indeed, Sloan (1943) observed lymphoid follicle formation in subjects with Addison's disease, acromegaly, and thyrotoxicosis.…”
Section: Correlation Of Histological Features Withmentioning
confidence: 99%